EFFECTS OF PERFORMANCE MANAGEMENT SYSTEM ON EMPLOYEE PERFORMANCE AND THE MODERATING ROLE OF STAFF DEVELOPMENT: THE CASE OF MINISTRY OF MINES AND MINERALS DEVELOPMENT IN ZAMBIA. - Meddiah , Munsaka; Wui, Charito (Human Resource and Leadership Journal, 2022)
The main aim of this paper is to investigate the effects of Performance Management System on Employee Performance in the Civil Service, specifically the Ministry of Mines and Minerals Development (MMMD) in Zambia. The research consists of four main parts: The effects of Performance Management System on Employee Performance; The effects of Performance Management System on Staff Development; The relationship between Staff Development and Employee Performance; and the mediating role of Staff Development on the effects of Performance Management System on Employee Performance. A quantitative approach was adopted in this study, with the population of interest consisting 250 employees who were randomly selected from six Departments under MMMD in Lusaka. The data was collected with the aid of structured questionnaires, and analysed using the Statistical Package for Social Sciences (SPSS) and excel. The findings of the research study indicates that Performance Management System: improves employee performance, efficiency and attitude towards work; identifies employee individual strengths and weaknesses; helps in identifying training needs and employee competencies; and also helps align employee qualifications/skills to the job requirements (job specifications). The research concludes that, Performance Management System has effects on Employee Performance and Staff Development. It also concludes that the relationship that exists between Staff Development and Employee Performance is that Staff Development enhances Employee Performance, which in turn improves career progression of employees as they acquire new knowledge and skills of doing their job. Further, the study concludes that Staff Development plays a reconciling role between Performance Management System and Employee Performance. The role played include: assisting employees gain knowledge and understanding of the job requirements, to enable them achieve the set performance standards and goals; facilitates for effective monitoring of employee performance; and helps to bridges gaps between identified employee incompetence and performance requirements.